Contraception for the HIV-Positive Woman: A Review of Interactions between Hormonal Contraception and Antiretroviral Therapy - Jennifer A. Robinson; Roxanne Jamshidi; Anne E. Burke (Hindawi Limited, 2012)
Background. Preventing unintended pregnancy in HIV-positive women can significantly reduce maternal-to-child HIV transmission as well as improve the woman's overall health. Hormonal contraceptives are safe and effective means to avoid unintended pregnancy, but there is concern that coadministration of antiretroviral drugs may alter contraceptive efficacy. Materials and Methods. We performed a literature search of PubMed and Ovid databases of articles published between January 1980 and February 2012 to identify English-language reports of drug-drug interactions between hormonal contraceptives (HCs) and antiretroviral drugs (ARVs). We also reviewed the FDA prescribing information of contraceptive hormone preparations and antiretrovirals for additional data and recommendations. Results. Twenty peer-reviewed publications and 42 pharmaceutical package labels were reviewed. Several studies of combined oral contraceptive pills (COCs) identified decreased serum estrogen and progestin levels when coadministered with certain ARVs. The contraceptive efficacy of injectable depot medroxyprogesterone acetate (DMPA) and the levonorgestrel intrauterine system (LNG-IUS) were largely unaffected by ARVs, while data on the contraceptive patch, ring, and implant were lacking. Conclusions. HIV-positive women should be offered a full range of hormonal contraceptive options, with conscientious counseling about possible reduced efficacy of COCs and the contraceptive implant when taken with ARVs. DMPA and the LNG-IUS maintain their contraceptive efficacy when taken with ARVs.